Spain : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Spanish economy suffered an unprecedented double-dip recession with the rising unemployment and public debt situation. Spain also suffered a reversal of private external financing flows in 2011 and 2012. To counter this situation, major policy actions have been taken in the banking sector. The fiscal framework has been improved, and a scheme for clearing subnational arrears has been established. The Executive Board emphasized the need for sustained efforts and a medium-term strategy for structural reforms and financial sector restructuring.